Review on Confidentiality, Integrity and Availability in Information Security - Kar Yee, Chai; Zolkipli, Mohamad Fadli (Journal of ICT in Education, 2021)
Information security is very significant needs to be secured due to people relying on networks and communication. Therefore, protecting information is a major challenge with the number of users increases rapidly in recent years. The aim of this article is to review Confidentiality, Integrity and Availability (CIA) in information security. This article focuses on the issues of information security and the requirements of information security. The articles, journals and conference papers are reviewed by researchers were published in 2016-2021. Security issues are analyzed in the recent methodologies. The result of the relationship between CIA in each information security requirement is at a moderate level. It is suggested cybersecurity risk awareness program for society is needed. Therefore, every user could get full advantages in networks and digital platforms.